Higher Spin Gauge Theories - Nicolas Boulanger (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This book collects various original contributions to the subject of higher spin gauge theory, as well as four review papers on the topic. The papers investigate the role of gauge fields with spin higher than two in the framework of classical and quantum field theories, the AdS/CFT correspondence and string theory.